2021
DOI: 10.3390/cells10123545
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Downstream mTORC1 Target Ribosomal Protein S6 Kinase (S6K) Can Be Found in a Subgroup of Dutch Patients with Granulomatous Pulmonary Disease

Abstract: Mechanistic target of rapamycin complex 1 (mTORC1) has been linked to different diseases. The mTORC1 signaling pathway is suggested to play a role in the granuloma formation of sarcoidosis. Recent studies demonstrated conflicting data on mTORC1 activation in patients with sarcoidosis by measuring activation of its downstream target S6 kinase (S6K) with either 33% or 100% of patients. Therefore, the aim of our study was to reevaluate the percentage of S6K activation in sarcoidosis patients in a Dutch cohort. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…In addition, they identified activation of this pathway in one third of granulomas obtained from 27 biopsies from sarcoidosis patients. Data from our own group confirmed these findings with the activation of the mTORC1 pathway seen in 43% of 74 Dutch sarcoidosis patients [7]. Furthermore, Linke et al [6] reported that by treating mice with everolimus, an mTOR inhibitor, the granuloma in the mice completely resolved.…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…In addition, they identified activation of this pathway in one third of granulomas obtained from 27 biopsies from sarcoidosis patients. Data from our own group confirmed these findings with the activation of the mTORC1 pathway seen in 43% of 74 Dutch sarcoidosis patients [7]. Furthermore, Linke et al [6] reported that by treating mice with everolimus, an mTOR inhibitor, the granuloma in the mice completely resolved.…”
Section: Introductionsupporting
confidence: 73%
“…Immunohistochemical staining procedure, as well as the used antibody for mTORC1 staining, was previously described in [ 7 ]. In order to study the role of the JAK/STAT signaling pathway in granuloma formation and pathogenesis of sarcoidosis, we performed immunohistochemical staining of the activated form of STAT1 and STAT3, phosphorylated STAT1 (p-STAT1) and p-STAT3 (Cell Signaling Technology, Inc., Danvers, MA, USA).…”
Section: Methodsmentioning
confidence: 99%